Groups, Communities, and Contested Identities in Genetic Research - Davis, Dena S. (The Hastings Center report, 2000)
Obtaining community consent before conducting genetic research seems to be a way of ensuring that a whole community is not harmed against its wishes—that all Jews, or all African Americans, or all Hutterites are not forced to learn things about themselves they would rather not know, or are not forced into identities they would rather not have. Unfortunately, there are insurmountable problems both in identifying the right representatives of the community and in obtaining their consent.